MANAJEMEN PESERTA DIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Ujang Andi Yusuf (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2019)
In the time of the development of various kinds of disciplines including the science of education, Islam was present as an ideal concept and a perfect model while answering various challenges from the various problems of the development of education. At a time when many Muslims themselves are unaware of the concepts and models of Islamic education and glare with theories, concepts, and models of non-Islamic education. Many institutions labeled Islam, but in reality are still far from the truth, so the graduates are still far from the hopes of the nation and Islam itself. Therefore, to print Islamic put out, it is necessary for the management of tarbiyah to design, organize, implement and control humans so that as students can maintain their nature when carrying out their main duties as khalīfah fī al-ardh to maintain the balance and continuity of life on this earth not damaged by dirty hands that have been damaged and even lost their nature in the form of religion and morals. This paper explains the meaning of management in Islam and aims to find out the management intentions of students in the perspective of Islamic education.Keywords: management, education, students.